2022
DOI: 10.1021/acs.est.1c07814
|View full text |Cite
|
Sign up to set email alerts
|

Is Urban Greening an Effective Solution to Enhance Environmental Comfort and Improve Air Quality?

Abstract: Urban greening has often been proposed as a cost-effective solution to improve environmental comfort, but may also deteriorate air quality. Quantifying these two opposing effects of urban greening is necessary to develop successful environmental policies for specific mega-city clusters. In this study, a high-resolution regional climate and air quality model (WRF-Chem, v4.0.3) was employed to test three scenarios aimed at quantifying the impact of land-use change and biogenic emissions from urban greening on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Studies have shown that global warming may increase the frequency and intensities of heatwaves and urban heat island effects, , such that the impacts of temperature-dependent AVOC emissions on ozone may become more pronounced in the future. Other underestimated or unrepresented natural and anthropogenic emissions of ozone precursors, such as soil-NO x emissions and emissions associated with urban greening practices, may also cause complex ozone-temperature sensitivities. These linkages between air pollution and meteorology should be considered in our projection of long-term air quality trends to better inform the long-term emission reduction goals.…”
Section: Uncertainties and Implications For Regional Air Quality Mana...mentioning
confidence: 99%
“…Studies have shown that global warming may increase the frequency and intensities of heatwaves and urban heat island effects, , such that the impacts of temperature-dependent AVOC emissions on ozone may become more pronounced in the future. Other underestimated or unrepresented natural and anthropogenic emissions of ozone precursors, such as soil-NO x emissions and emissions associated with urban greening practices, may also cause complex ozone-temperature sensitivities. These linkages between air pollution and meteorology should be considered in our projection of long-term air quality trends to better inform the long-term emission reduction goals.…”
Section: Uncertainties and Implications For Regional Air Quality Mana...mentioning
confidence: 99%
“…Besides, green infrastructure serves as a significant source of ESs supply, offering various benefits such as cooling (Li et al 2022;Zhou et al 2021) and the enhancement of air quality (Yu et al 2022) within urban areas. It's worth noting that studies have revealed that using low-resolution data can lead to underestimations in green space assessment (Qian et al 2020).…”
Section: Uncertainties and Limitationsmentioning
confidence: 99%
“…The spatial concentration of a large number of industrial enterprises leads to an increase in the total amount of industrial pollutants discharged in the region and an increase in the degree of environmental damage (Li H et al, 2020;Panda and Siva Nagendra, 2018), and is therefore measured by the ratio of the number of industrial enterprises above the scale to the area of the jurisdiction (Lin et al, 2022). 7) Vegetation index (NDVI): in this paper, the normalized difference vegetation index (NDVI) is used to measure the level of urban greening, which may have both positive and negative effects on air quality; on the one hand, green areas as carbon sinks can play a role in purifying the air, and on the other hand, excessive investment in urban green areas may crowd out environmental protection expenditures in other areas (Yu et al, 2022).…”
Section: Data Settingsmentioning
confidence: 99%